2010
DOI: 10.1080/14786410903211912
|View full text |Cite
|
Sign up to set email alerts
|

A cardiac glucoside within vitroanti-HIV activity isolated fromElaeodendron croceum

Abstract: Human immunodeficiency virus (HIV) affects more than 40 million people worldwide and more than 5 million in South Africa alone. There is no cure for the disease yet, and novel effective drugs need to be discovered to make any progress in combating the disease. Twelve extracts from indigenous South African plants were analysed, of which Elaeodendron croceum showed potent inhibition of transcription factors and a recombinant HIV strain in an MT-2 VSV-pseudotyped recombinant virus assay at 100 ng mL(-1). Bioassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…The possibility of repurposing drugs already used in humans as novel therapeutics for the control of HIV-1 infection is highly attractive. Our findings agree with a recent study which identified multiple CSs as inhibitors of HIV-1 expression 45 , 51 . Our study confirms that ≥ 5 of the reported hits and 7 additional CSs suppress HIV-1 gene expression in transformed cells [HeLa and CD4 + SUPT1s, Supplementary Figs S2 (or Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The possibility of repurposing drugs already used in humans as novel therapeutics for the control of HIV-1 infection is highly attractive. Our findings agree with a recent study which identified multiple CSs as inhibitors of HIV-1 expression 45 , 51 . Our study confirms that ≥ 5 of the reported hits and 7 additional CSs suppress HIV-1 gene expression in transformed cells [HeLa and CD4 + SUPT1s, Supplementary Figs S2 (or Fig.…”
Section: Discussionsupporting
confidence: 93%
“…); saffraan, bossafraan (Afr.) Leaves, bark, roots Cleaning of the digestive tract, chest congestion [ 34 , 35 ]. PRU 120127 Morus mesozygia Moraceae Black mulberry or African mulberry Leaves, bark, roots Arthritis, debility, malnutrition, gastroenteritis, rheumatism, venereal diseases, wound infections, dermatitis, syphilis, malaria, fever, pain, depression, peptic ulcers [ 48 ] PRU 120128 …”
Section: Methodsmentioning
confidence: 99%
“…Compounds stabilizing the firefly luciferase reporter protein give false positives. (Auld et al, 2008;Cos et al, 2002;Ngwira et al, 2015;Prinsloo et al, 2010;Shoemaker et al, 2004;Sotoca et al, 2010;Wang et al, 2014) NF-κB activation assay Cells are stably transfected with a plasmid containing the firefly luciferase gene driven by the HIV-LTRpromoter, highly dependent on NF-κB activation induced by TNFα. High expression of luciferase activity reflects NF-κB activation through the canonical pathway.…”
Section: Constituents With Antioxidant Activity Results In Toomentioning
confidence: 99%
“…Thereby, upon infection with HIV, the reporter gene will be induced in a quantifiable fashion as beta galactosidase allows quantification of inhibitory effects of compounds or extracts (Lubbe et al, 2012). HIV-1 pseudovirions and viruses has been used (Ngwira et al, 2015;Prinsloo et al, 2010;Wang et al, 2014) and Hela-Tat-Luc cells that are stably transfected with for instance a plasmid pcDNA3-TAT together with a reporter plasmid LTR-Luc indicates protein activation. Therefore the HIV-1 LTR is highly activated in this cell line as a consequence of high levels of intracellular Tat protein (Tshikalange et al, 2008b).…”
Section: Constituents With Antioxidant Activity Results In Toomentioning
confidence: 99%